A sustainable nanocomposite for removal of heavy metals from water based on crosslinked sodium alginate with iron oxide waste material from steel industry. Issue 4 (August 2020) - Mahmoud, Mohamed E.; Saleh, Mohamed M.; Zaki, Mohamed M.; Nabil, Gehan M.
Graphical abstract: Highlights: Iron oxide fine by-product has been crosslinked with sodium alginate. Factors optimization of three heavy metals removal. Evaluation of different adsorption kinetics and isotherm models. Successful removal of heavy metals from water by the sustainable nanocomposite. Abstract: Industrial activities with zero waste have been recently targeted for the sake of cleaner environment. Therefore, industrial wastes are recycled and reused in self-manufacturing processes or employed in other industrial sectors and applications. In this work, steel industrial waste material such as iron oxide fine powder was utilized to remove some heavy metal such as lead, cadmium and copper from water. Iron oxide waste was grinded to produce iron oxide waste nanoparticles (IOWNPs) and was crosslinked to alginate as a biodegradable polymer to produce IOWNPs-Alg nanocomposite. The nanocomposite structure was validated using FTIR, SEM, TEM, TGA and XRD. The equilibrium sorption was obtained after 30 min with maximum capacities for lead, copper and cadmium; 564 mg g −1, 158 mg g -1 and 102.2 mg g −1, respectively. Adsorption behaviors were investigated using five isotherm models. The pseudo -first order, pseudo -second order, Elovich, intraparticle diffusion and Bangham`s kinetic models were used for kinetic behavior evaluations. The adsorption kinetic study referred to satisfactory adsorption of cadmium via pseudo -first order, while pseudo -second order was the best model to describe adsorption of copper and lead ions onto IOWNPs-Alg nanocomposite. The adsorption behaviors of evaluated heavy metal ions were found to obey Freundlich isotherm model and confirm surface heterogeneity and exponential distribution of active sites. The assembled IOWNPs-Alg nanocomposite was further confirmed as an effective nanosorbent for removal of lead, cadmium and copper from wastewater samples.